Di Luar Keuntungan: Bagaimana Struktur Modal, Profitabilitas, dan Pelaporan Keberlanjutan Membentuk Nilai Perusahaan dengan Efek Moderasi Tata Kelola Perusahaan yang Baik - Firra Nurisma; Sovi Ismawati Rahayu; Hestin Agus Tantri Ningsih (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
This study examines the influence of capital structure, profitability, and sustainability reporting on firm value, with the independent board of commissioners as a moderating variable. The phenomenon underlying this research is the fluctuation in firm value among companies listed in the LQ45 Index during 2019–2024 despite their strong market capitalization and liquidity. The study uses secondary data obtained from annual reports and sustainability reports of 14 companies selected through purposive sampling, resulting in 84 data observations. Capital structure is measured by Debt-to-Equity Ratio (DER), profitability by Return on Assets (ROA), sustainability reporting by Sustainability Report Disclosure Index (SRDI), and firm value by Price to Book Value (PBV). Data was analyzed using panel data regression and Moderated Regression Analysis (MRA). The results indicate that profitability has a positive and significant effect on firm value, while capital structure and sustainability reporting do not significantly affect firm value. Furthermore, the independent board of commissioners strengthens the relationship between profitability and firm value but does not significantly moderate capital structure and sustainability reporting. These findings suggest that effective corporate governance enhances the contribution of financial performance to firm value and provides managerial insight for companies in improving investor confidence through stronger governance practices